2018
DOI: 10.3389/fphar.2018.00661
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Leaves of Annona muricata L. as a Source of Potential Anti-inflammatory and Anticancer Agents

Abstract: The use of anti-inflammatory natural products to treat inflammatory disorders for cancer prevention and therapy is an appealing area of interest in the last decades. Annona muricata L. is one of the many plant extracts that have been explored owing to their anti-inflammatory and anticancer effects. Different parts of A. muricata especially the leaves have been used for various ethnomedicinal purposes by traditional healers to treat several diseases including cancer, inflammation, diabetes, liver diseases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 140 publications
0
40
1
4
Order By: Relevance
“…The results revealed that administration as from 8 g/ml/Kg bw for Annona muricata leaves and 6 g/ml/Kg bw for Fagara zanthoxyloide roots resulted in signs of toxicity and oral administration below this levels was well tolerated in mice even beyond 7 days. The result for the toxicity of Annona muricata was however slightly higher than the findings by [4] in which he observed kidney toxicity above 5 g/Kg bw and [25] who observed 100% mortality at 5 g/Kg bw with Annona muricata from Benin was investigated. Fagara zanthoxyloide acute toxicity test resulted in signs of toxicity as from 6 g/Kg bw with animals witnessing weight loss, lacrimation and reduced irritability ( Table 7).…”
Section: Acute Toxicity (Ld 50 )contrasting
confidence: 63%
See 2 more Smart Citations
“…The results revealed that administration as from 8 g/ml/Kg bw for Annona muricata leaves and 6 g/ml/Kg bw for Fagara zanthoxyloide roots resulted in signs of toxicity and oral administration below this levels was well tolerated in mice even beyond 7 days. The result for the toxicity of Annona muricata was however slightly higher than the findings by [4] in which he observed kidney toxicity above 5 g/Kg bw and [25] who observed 100% mortality at 5 g/Kg bw with Annona muricata from Benin was investigated. Fagara zanthoxyloide acute toxicity test resulted in signs of toxicity as from 6 g/Kg bw with animals witnessing weight loss, lacrimation and reduced irritability ( Table 7).…”
Section: Acute Toxicity (Ld 50 )contrasting
confidence: 63%
“…Notably, the leaves have been used traditionally in the treatment cystitis, diabetes, insomnia and headaches [2], coughs, skin diseases and pains [3]. According to [4], the roots have been acclaimed to have antiinflammatory and anthelmintic potentials [5]. They leaves, fruits and roots have also been used as insecticides and pesticide agents among Africans as well as insect repellants [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, acetogenins possess a broad spectrum of biological effects such as antineoplastic, antiparasitic, insecticidal, and immunosuppressive activities. These compounds exhibit their potent bioactivities through the depletion of ATP levels by inhibiting complex I of the mitochondria and NADH oxidase of the plasma membranes of tumor cells (Abdul-Wahab et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Several phytochemicals, such as acetogenin derivatives in A. muricata leaves have shown neurotoxicity (coreximine with EC 50 at 13 µM, reticuline EC 50 at 304 µM and annonacin EC 50 at 0.018 µM) in vitro and in vivo studies due to its viability reduction of mesencephalic dopaminergic neurons (Lannuzel et al, 2003, Wahab et al, 2018. However, it has been investigated that the synergistic interactions among flavonoids and acetogenins in A. muricata leaves confer protection against prostate cancer (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%